Development of Green Polymer: Effect of CTAB-Modified Bentonite Addition on the Thermal Properties and Impact Toughness - Santoso, Teguh Budi; Sari, Shaila Iffani Fatiha (Universitas Mulawarman, 2025)
The concept of green polymer has gained increasing attention due to its potential to reduce environmental impacts through the use of recycled materials and natural fillers. This study investigates how the addition of Cetyl Trimethyl Ammonium Bromide (CTAB)-modified bentonite influences the thermal behavior and impact toughness of recycled polypropylene (rPP) composites. The composites were prepared with 0 wt%, 3 wt%, and 5 wt% CTAB-modified bentonite. Thermal analysis was performed using Differential Scanning Calorimetry (DSC), while impact toughness was determined using the Charpy method. The results showed that 5 wt% CTAB-modified bentonite increased the melting temperature (Tm) to 165.9 °C, whereas 3 wt% yielded the highest impact toughness of 17.65 kJ/m². The highest crystallinity (51.23%) was obtained in the sample without filler. Therefore, the incorporation of CTAB-modified bentonite not only enhances the thermal and mechanical performance of recycled PP but also promotes the development of environmentally friendly green polymers.